2012
DOI: 10.1177/0018726712460706
|View full text |Cite
|
Sign up to set email alerts
|

Organizational ethical climate, perceived organizational support, and employee silence: A cross-level investigation

Abstract: This article reports on a study investigating the cross-level relationships of organizational ethical climate on employee silence. Using a sample of 408 full-time employees from 24 high-technology firms in Taiwan, the study conducted multilevel analyses to examine its hypotheses. The results showed that instrumental climate – one type of organizational ethical climate – had a positive association with acquiescent silence, but not with defensive silence. Another two types of organizational ethical climate – car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 47 publications
4
142
0
6
Order By: Relevance
“…It is worth noting that the literature indicates such altruism is more evident if money is to be sent to colleagues or charitable institutions. As such, individual and situational factors may be combining (Wang and Hsieh 2013), this was also found in the work of Chmura et al (2010) where a higher altruism rate is also observed for prisoners from the same correctional facility. In the context of our study, the work environment stimulates a 'team spirit' that leads employees to feel closer to each other compared to other randomly matched subjects in other studies.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…It is worth noting that the literature indicates such altruism is more evident if money is to be sent to colleagues or charitable institutions. As such, individual and situational factors may be combining (Wang and Hsieh 2013), this was also found in the work of Chmura et al (2010) where a higher altruism rate is also observed for prisoners from the same correctional facility. In the context of our study, the work environment stimulates a 'team spirit' that leads employees to feel closer to each other compared to other randomly matched subjects in other studies.…”
Section: Resultsmentioning
confidence: 52%
“…Situational factors affect an employee's individual sense of right and wrong when, in our setting, they encounter operational risk events, and this forms shared beliefs, norms and common practices regarding the management of error reporting in the organisation (Van Dyck et al 2005). Thus, the interaction of the situational and the individual can lead an individual to make a decision to remain silent and ignore reporting important error events occurring around them (see Wang and Hsieh 2013) or actually undertaken by them (see Zhao and Olivera 2006). Action or inaction is important within a work climate, where positive action, if viewed favourably by leaders, might be emulated by other members of a group (Haidt 2000(Haidt , 2003Romani and Grappi 2013) as previously discussed in relation to risk reporting by Bryce et al (2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A grande parte das pesquisas estão relacionadas à métodos de diagnósticos de clima, ensaios teóricos e/ou correlação de clima organizacional com algum aspecto da organização (Oliva et al, 2007), tais como: mutismo (Wang e Hsieh, 2013), cultura organizacional (Kolb, 1978;Quinn, 1984;Sá et al, 2006), inovação (Imran et al, 2010), estresse (Puente-Palacios et al, 2013), qualidade de vida (Rueda et al, 2013), dentre outros.…”
Section: As Dimensões Comuns Aos Trabalhos Sãounclassified
“…However, there were majority of studies showed that employee silence had negative impact on employee motivation, and ultimately resulted in job burnout (Cai & Geng, 2016).Therefore, it is necessary to discover more antecedents of employee silence and eliminate the negative effect. The current research has focused on some positive antecedents, which reduce employee silence, such as trust (Zheng et al,2008),perceived supervisor support (Li & Ling, 2010), perceived organizational support (Wang & Hsieh, 2013) and well-being (Knoll & Dick, 2013). Scarce research has examined the effect of negative antecedents on employee silence, which mainly focused on abusive supervision .Abusive supervision refers to "subordinates" perceptions of the extent to which their supervisors engage in the sustained display of hostile verbal and nonverbal behaviors, excluding physical contact" (Tepper, 2007).Research to date has little focused on the relationship between supervisor incivility and employee silence, especially in China .Supervisor incivility has been defined as supervisor"s low intensity deviant behavior with ambiguous intent to harm the subordinate, in violation of workplace norms for mutual respect (Anderson & Pearson, 1999, p.452).…”
Section: Introductionmentioning
confidence: 99%